Batteries charging systems for electric and plug-in hybrid electric vehicles - Monteiro, Vítor Duarte Fernandes (2012)
Many countries have a large dependence on imported fossil fuels whose prices increase almost every day. Knowing that much of this consumption is for transportation systems, it becomes essential to seek for alternatives. The natural bet is the electric mobility, namely through Electric Vehicles (EVs) and Plug-in Hybrid Electric Vehicles (PHEVs). However, the wide spread utilization of these vehicles has consequences on the electrical power grid, mainly in terms of load management and electric power quality, which are associated to the batteries charging systems. In this scenario, this chapter assesses the electric mobility integration in Smart Grid context, focusing different approaches to the operation of EVs and PHEVs charging processes and the specifications of the chargers, as well as different topologies of charging systems and their features, modes of operation, typical waveforms, and impact in the electrical power grid in terms of power quality. It is also presented a laboratory prototype of a bidirectional EV charger and shown some experimental results. This prototype was developed to charge the batteries aiming to preserve their lifespan, and to contribute to mitigate the degradation of the power quality. The experimental results show the operation of this prototype during the batteries charging process (G2V – Grid-to-Vehicle operation), and during the delivering of stored energy back to the electrical power grid (V2G – Vehicle-to-Grid operation).